Modeling of a low-temperature gas treatment system - M. P. Kuznetsov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The main purpose of the work is: investigation of the effect of changes in technological parameters on the efficiency of the separation process and determination of optimal technological modes of operation of gas field X CNTS in the separation process.Method. The problem was solved in the KBC Petro-SIM computer program and the LTS model was built. To conduct the study, a model of the LTS was built in the KBC Petro-SIM computer program.Result. The results obtained with the help of it showed: with the current composition of the gas with a decrease in temperature for every 2oC, with other technological indicators being equal, the specific condensate yield increases in the range from 15 to 30%, and the lower the temperature, the higher this percentage. When the pressure on the throttle decreases by every 0.4 MPa, the condensate output increases, if the pressure drops below 1.8 MPa, the specific condensate output will begin to decrease, which is explained by the pressure drop below the maximum condensation line of the phase diagram. The change in gas flow within the design values did not affect the operation of low-temperature separation. At any available low temperature and high pressure at the inlet to the ILTS, the most optimal mode will be when the pressure after the throttle is maintained within 1.8 - 1.9 MPa. The maximum specific yield of gas condensate (48.21%) was obtained at a pressure at the inlet to the ILTS of 5.1 MPa, a temperature after the heat exchanger of minus 2oC and a pressure drop at the throttle of 3.05 MPa. As part of the numerical research, the following results were obtained: with an increase in the pressure at the inlet to the ILTC, the change in the specific output of the gas condensate is insignificant, but with this parameter it is possible to create a larger pressure drop on the throttle; with a decrease in the gas temperature at the outlet of the heat exchanger, the specific yield of the gas condensate will increase; with an increase in the pressure drop at the throttle, the specific output of the gas condensate increases until the pressure after the throttle reaches the range of values of 1.8 – 1.9 MPa. In this interval, the maximum specific condensate yield is achieved. With a further increase in the pressure drop on the throttle, the specific output of the gas condensate decreases. This is explained by the phenomenon of retrograde condensation, since the maximum condensation line is in the range of these pressures.Conclusion. Based on the results of the work, it was found that the developed software module can be used to solve the emerging series of problems. The results of the work show the suitability of the proposed method for practical purposes.